The DNA methyltransferase family: a versatile toolkit for epigenetic regulation - Lyko, Frank (Nature reviews. Genetics, 2018)
The DNA methyltransferase (DNMT) family comprises a conserved set of DNA-modifying enzymes that have a central role in epigenetic gene regulation. Recent studies have shown that the functions of the canonical DNMT enzymes — DNMT1, DNMT3A and DNMT3B — go beyond their traditional roles of establishing and maintaining DNA methylation patterns. This Review analyses how molecular interactions and changes in gene copy numbers modulate the activity of DNMTs in diverse gene regulatory functions, including transcriptional silencing, transcriptional activation and post-transcriptional regulation by DNMT2-dependent tRNA methylation. This mechanistic diversity enables the DNMT family to function as a versatile toolkit for epigenetic regulation.